An Overview of different Business Models for public Wi-Fi and their Implications on Indirect Revenue - Tobias Werner Kaiser; Sofie Verbrugge; Marlies Van der Wee; Didier Colle (International Telecommunications Society (ITS), 2017)
The importance of public Wi-Fi for providing service to customers and mobile data offloading is steadily increasing. This paper aimed at analyzing the business model of select cases of customer-facing and municipal Wi-Fi networks with respect to physical setting, network ownership, service provisioning, (in)direct revenues, and cooperational benefits. Depending on the setting, different sources of indirect revenue can be identified, in particular with respect to the difference between customer-facing and municipal Wi-Fi. By comparing the cases according to these parameters, the paper concludes that successful public Wi-Fi projects make extensive use of cooperational benefits, as they reduce the economic difficulty of public Wi-Fi deployment by keeping costs low, increasing indirect revenue, and decreasing the likelihood of lawsuits against municipalities, therefore contributing to the formation of free municipal Wi-Fi. In municipal Wi-Fi, these benefits emerge as a result of the distinction between network owner and service provider. Instead of relying on tax-funded public service provisioning and possibly risking a lawsuit on the grounds of distorting competition, municipal Wi-Fi initiatives should therefore seek to cooperate with private ISPs.
Keywords: 330; public Wi-Fi; municipal Wi-Fi; cooperation; indirect effects; indirect revenue; business models